Structure and Monitoring in the Seismic Activation Zone of the Gorlovskaya Depression of the Altai-Sayan Folded Region According to Electrical Resistivity Tomography Data - Nevedrova Nina; Shalaginov Aleksandr Evgen'evich; Shaparenko Il'ya Olegovich; Sanchaa Aydisa; Marinenko Arkadiy Vadimovich (Russian Journal of Earth Sciences, 2024)
In the last decade, the intensity of development of the Gorlovskoye coal deposit has increased significantly, which leads to the formation of seismic activation of the subsoil of the Gorlovka depression in response to man-made impact. Since 2019, earthquakes with a magnitude of more than 4 have been recorded in the area of the deposit, felt in Novosibirsk and its suburbs. The main objective of the study: as data accumulates, to identify the criteria for seismic activations using one of the methods of ground-based electrical exploration – electrical resistivity tomography. The article considers the geoelectric structure of the Gorlovka depression in the area of the transition from its deposits to the Salair ridge, and also analyzes the results of monitoring carried out in 2023 by the electrical resistivity tomography method along a profile intersecting one of the fault structures. The monitoring observation profile is located on a site selected during experimental and methodological work and is located just a few kilometers from coal quarries and the zone of concentration of seismic events. It was found that the identified variations in geoelectric parameters reflect the reaction of the geological environment not only to earthquakes occurring during the observation period, but also to man-made impacts (explosions).